Relevance of cooperative learning about the different profiles of the bullying dynamic. An analysis by testing the effect size - León del Barco, Benito; Polo del Río, María-Isabel; Gozalo Delgado, Margarita; Mendo Lázaro, Santiago (Anales de Psicología / Annals of Psychology, 2015)
With this research we try to determine which dynamic profile bullying (Aggressor, Victim, Observer) is more relevant in cooperative learning intervention. We will use evidence of effect size. In order to assess bullying behaviors have designed an instrument "Frequency Scale Peer Bullying. Perspective Aggressor, Victim and Observer". We have worked with two groups of participants in the 3rd cycle of primary, a first group of 311 students we used for the psychometric analysis of the instrument and a second group of 110 students for intervention. Our results show that the inter-group effect size was high for the social exclusion factor for observer profiles (d = 0.64) and aggressor (d = 0.65). Also, get a higher size factor direct verbal and physical attacks on observer profile (d = 0.57). In synthesis, after the analysis of the effect size we found that cooperative learning is effective on the offender profile and especially on the observe.